Shifting discussions to the supranational level: a narrative discourse analysis on nuclear energy sustainability and the EU Taxonomy - Carsten Elsner (Energy, Sustainability and Society, 2024)
Abstract Background While discussions on nuclear energy mostly took place at the national level and the respective media arenas in the past, the questions of regulating sustainability and financing have now moved up to the supranational EU level. In this light, this article analyses the discussions and processes around the inclusion of nuclear energy into the EU Taxonomy, which aims at guiding financial means towards sustainable economic activities. Results The research question as to why nuclear energy has become sustainable is examined by applying a narrative discourse analysis. To account for the identified challenges for media-based discourse analysis regarding nuclear energy, an analysis was conducted alongside key events relying on media articles and expert interviews, following the institutional structure of the implementation process. The article contributes to the limited body of literature on sustainability regulation, particularly from a social science perspective. By delving into the specific dimensions of the regulatory process on nuclear energy, it provides a nuanced understanding that enriches existing academic discourse in this emerging field. Conclusions In the article, it is argued that four factors contributed mainly to the decision to label nuclear energy sustainable: the delegated act, combined with the decision to connect nuclear energy and gas (1), the publication of the report by the Joint Research Centre (2), the implicit compromise between Germany (gas) and France (nuclear energy) (3) and finally, the Russian war against Ukraine (4). Although narrative discourse analysis still offers valuable insights into ongoing policy processes at the EU level, the different implementation process in the EU by means of the delegated act shapes its explanatory power compared to the national context.